HYPOXIA-HYPEROXIA ADAPTATION AND INCREASED EXERCISE CAPACITY IN PATIENTS WITH CORONARY HEART DISEASE - O. S. Glazachev; Yu. M. Pozdnyakov; A. M. Urinskyi; S. P. Zabashta (Кардиоваскулярная терапия и профилактика)
Aim. To assess effectiveness and safety of a new rehabilitation method — interval hypoxia-hyperoxia training (IHHT) — in patients with chronic coronary heart disease (CCHD).Material and methods. This pilot study included 40 CCHD patients, Functional Class II–III (31 men and 9 women; mean age 61,7±7,7 years). The IHHT group (n=30) underwent 20 procedures (duration 40–50 minutes, 5 times a week), while the control group (n=10) underwent 20 similar placebo procedures. The REOXY device (AIMediqS.A., Luxemburg) was used for the creation of the gas mixtures with O2 content from 10% to 35–40%. At baseline and in the end of the treatment, individual hypoxia sensitivity was assessed in a 10-minute hypoxic test (HT). The IHHT procedure started with 5–7 minutes of mask inhalation of 12–11% О2, followed by 2–3 minutes of mask inhalation of 30% O2. The automatic switch between the gas mixtures followed the biological feedback principle; one procedure included 6–8 hypoxiahyperoxia cycles. Before and after the intervention phase, all participants underwent clinical and biochemical blood assay, rest ECG, submaximal treadmill test (time of the test, workload, and exercise capacity in metabolic equivalent units (MET)).Results. After the IHHT course, the main group demonstrated a significant increase in exercise capacity: test time increased by 34,1% (vs. —2,7% in controls), while exercise capacity (MET) increased by 15,8% (vs. 5,4% in controls), and the prevalence of angina attacks as the result of test termination significantly decreased. Improved exercise capacity was associated with a significant reduction in total cholesterol, plasma triglycerides, initially elevated blood pressure and resting heart rate, as well as with an elevated hypoxia tolerance threshold in the HT. In all participants, IHHT was well tolerated and free from adverse effects. Conclusion. The IHHT method increases exercise capacity in CCHDpatients, which is associated with lipid profile normalisation, blood pressure reduction, decreased number of angina attacks, and increased resistance to hypoxia.